Evidence based medicine manifesto for better healthcare. (20th June 2017) - Heneghan, Carl; Mahtani, Kamal R; Goldacre, Ben; Godlee, Fiona; Macdonald, Helen; Jarvies, Duncan
Abstract : A response to systematic bias, wastage, error, and fraud in research underpinning patient care